Progressive reparative gliosis in aged hosts and interferences with neural grafts in an animal model of Huntington's disease - Mazurová, Yvona; Látr, Ivan; Osterreicher, Jan; Guncová, Ivana (Cellular and molecular neurobiology, 2006)
1. Neural transplantation in Huntington's diseased patients is currently the only approach in the treatment of this neurodegenerative disorder. The clinical trial, unfortunately, includes only a small number of patients until now, since many important questions have not been answered yet. One of them is only mild to moderate improvement of the state in most of grafted patients. 2. We examined the morphological correlates in the response to intrastriatal grafting of fragments of foetal rat ventral mesencephalic tissue 1 month after transplantation in male Wistar rats within varying durations (from 2 to 38 weeks) of experimentally induced neurodegenerative process of the striatum (used as a model of Huntington's disease). Our goal was to determine the impact of advanced striatal damage and gliosis on the graft viability and host-graft integration. 3. The findings can be summarized as follows: The progressive reactive gliosis, which is not able to compensate continual reduction of the grey matter leading to an extensive atrophy of the striatum in a long-term lesions, results in formation of the compact glial network. This tissue cannot be considered the suitable terrain for successful graft development and formation of host-graft interconnections. 4. The progression of irreversible morphological changes in long-lasting neurodegenerative process within the striatum can be supposed one of the important factors, which may decrease our prospect of distinct improvement after neural grafting in patients in advanced stage of Huntington's disease, who still remain the leading group in clinical trials.
Keywords: modely nemocí na zvířatech; Transplantation; Male; Rats, Wistar; progrese nemoci; bazální ganglia; Fetal Tissue Transplantation; Huntingtonova nemoc; Age Factors; Gliosis; transplantace mozkové tkáně; mužské pohlaví; Disease Progression; potkani Wistar; Huntington Disease; transplantace; Brain Tissue Transplantation; krysa rodu Rattus; Animals; transplantace fetální tkáně; Basal Ganglia; zvířata; Rats; Disease Models, Animal; věkové faktory; glióza